Implantasi CRT pada Pasien dengan Katup Thebesian Prominen - Erwin Mulia; Wenny Fitrina Dewi; Erika Maharani; Yoga Yuniadi (The Indonesian Heart Association, 2011)
CRT has been established as standard treatment for refractory heart failure in many major clinical trials. Insertion of left ventricle lead is frequently most challenging step. Coronary sinus anatomy is of the most technical burden. A case of CRT implantation with presence of prominent Thebesian valve and stenotic posterolateral vein is presented in thic case report.